2012
DOI: 10.1073/pnas.1210285109
|View full text |Cite
|
Sign up to set email alerts
|

Acid–base chemical reaction model for nucleation rates in the polluted atmospheric boundary layer

Abstract: Climate models show that particles formed by nucleation can affect cloud cover and, therefore, the earth's radiation budget. Measurements worldwide show that nucleation rates in the atmospheric boundary layer are positively correlated with concentrations of sulfuric acid vapor. However, current nucleation theories do not correctly predict either the observed nucleation rates or their functional dependence on sulfuric acid concentrations. This paper develops an alternative approach for modeling nucleation rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
285
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 186 publications
(293 citation statements)
references
References 46 publications
8
285
0
Order By: Relevance
“…(Indeed, an analogous approach recently applied to atmospheric field measurements was much more successful than traditional analyses for predicting new particle formation from sulfuric acid in air; see ref. 22.) It is noteworthy that our results suggest that rates of new particle formation can be a complex function of not only the nature and concentration of the precursors, including water, but also which precursor specifically is the "limiting reagent."…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…(Indeed, an analogous approach recently applied to atmospheric field measurements was much more successful than traditional analyses for predicting new particle formation from sulfuric acid in air; see ref. 22.) It is noteworthy that our results suggest that rates of new particle formation can be a complex function of not only the nature and concentration of the precursors, including water, but also which precursor specifically is the "limiting reagent."…”
Section: Discussionmentioning
confidence: 98%
“…This theory has been applied to particle formation in relatively simple systems and clusters of relatively few molecules. Recent data from field and laboratory studies, however, suggest that multicomponent systems with multiple reaction steps are likely involved in new particle formation in the atmosphere (14)(15)(16)(17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%
“…28 in the same flow tube. Another experiment 15 measured high dimer formation rates linked to amine mixing ratios of about 1 part per billion by volume and above. Our results directly link high concentrations of neutral H 2 SO 4 dimer with amines at atmospheric levels.…”
mentioning
confidence: 99%
“…Amines have already been predicted as likely candidates enhancing the nucleation rates based on quantum-chemical studies 8,9 and it has been observed that they contribute in the formation of secondary aerosol 10,11 . Laboratory studies as well as atmospheric measurements have also revealed that amines enhance ternary nucleation [12][13][14] . In addition, a recent CLOUD (Cosmics Leaving OUtdoor Droplets) chamber study was able to show that the ternary H 2 SO 4 -H 2 O-DMA (DMA, dimethylamine, (CH 3 ) 2 NH) system can explain atmospheric boundary layer nucleation events for atmospherically relevant concentration of sulfuric acid and dimethylamine under certain conditions 15 .…”
Section: Ternary H 2 So 4 -H 2 O-dimethylamine Nucleationmentioning
confidence: 99%